The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41467-021-21866-1
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion of subducted crust explains the emplacement of far-travelled ophiolites

Abstract: Continental subduction below oceanic plates and associated emplacement of ophiolite sheets remain enigmatic chapters in global plate tectonics. Numerous ophiolite belts on Earth exhibit a far-travelled ophiolite sheet that is separated from its oceanic root by tectonic windows exposing continental crust, which experienced subduction-related high pressure-low temperature metamorphism during obduction. However, the link between continental subduction-exhumation dynamics and far-travelled ophiolite emplacement re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…In this scenario, the Paleogene burial can be related to the obduction of an oceanic lithosphere connected with a hyper‐extended continental margin over the continental NFC. The obduction of oceanic lithosphere or arc‐continent collisions are commonly associated with regional burial metamorphism of continental margins (e.g., Agard & Vitale‐Brovarone, 2013; Goffé et al., 1988; Porkoláb et al., 2021; Pourteau et al., 2013; van Hinsbergen et al., 2016). In this scenario, the Paleogene white mica 40 Ar/ 39 Ar ages of the relic S 0‐1 foliation in the continental Calar‐Alto unit can be explained by burial metamorphism during the obduction of the Ophiolite unit (Figure 11c), whose record is preserved only in the deeper sections of the Calar‐Alto unit, at far distances from the Miocene shear zones (Figures 7a and 8g).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, the Paleogene burial can be related to the obduction of an oceanic lithosphere connected with a hyper‐extended continental margin over the continental NFC. The obduction of oceanic lithosphere or arc‐continent collisions are commonly associated with regional burial metamorphism of continental margins (e.g., Agard & Vitale‐Brovarone, 2013; Goffé et al., 1988; Porkoláb et al., 2021; Pourteau et al., 2013; van Hinsbergen et al., 2016). In this scenario, the Paleogene white mica 40 Ar/ 39 Ar ages of the relic S 0‐1 foliation in the continental Calar‐Alto unit can be explained by burial metamorphism during the obduction of the Ophiolite unit (Figure 11c), whose record is preserved only in the deeper sections of the Calar‐Alto unit, at far distances from the Miocene shear zones (Figures 7a and 8g).…”
Section: Discussionmentioning
confidence: 99%
“…Ophiolites not only contain records of spreading ridges, but also relics of subduction interfaces in the form of metamorphic soles (Guilmette C. et al, 2018;Hacker et al, 1996), as well as transform faults (Allerton, 1989;Morris and Maffione, 2016). But because ophiolites form and are uplifted at plate boundaries, they typically are dismembered, displaced, and eroded klippen that form the structurally highest thrust sheet in fold-thrust belts (e.g., Maffione et al, 2015;Porkoláb et al, 2021;Robertson, 2002). With rare exceptions such as in the Semail ophiolite of Oman that covers an area of more than 20,000 km 2 (Nicolas et al, 2000), the original coherence of these klippen as an ocean floor cannot be directly established from field observations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, using 2-D thermo-mechanical models, Duretz et al (2016) studied the obduction process of Oman ophiolite, which indicated that a thermal anomaly in the oceanic lithosphere near the continental margin along with a strong continental crust is required for the emplacement of the ophiolite. Moreover, Porkoláb et al (2021) studied the relationship between the subduction-exhumation process and emplacement of far-traveled ophiolite. They further proposed that extrusion of the subducted continental margin driven by buoyancy is critical, and controls the emplacement of far-traveled ophiolitic sheet.…”
mentioning
confidence: 99%